How Should We Prepare Our Pharmacist Preceptors? Design, Development and Implementation of a Training Program in a Regional Australian University - Gillian J. Knott; Martina F. Mylrea; Beverley D. Glass (MDPI AG, 2023)
Increased experiential learning within pharmacy education has highlighted the need for quality preceptors, leading to a recent focus on their development and training. This study describes the design, development and implementation of a pharmacist preceptor training program in a regional Australian University. The design of this program utilized the results of a previously conducted scoping review of preceptor training programs and a comprehensive preceptor training needs analysis. In addition, participation was sought from an expert advisory group, comprising preceptors and pharmacy professional organizations. Program materials were developed and transferred onto a suitable online learning platform for implementation. Post-training program evaluation will follow Kirkpatrick's model of training evaluation criteria, gaining feedback from both preceptors and students. The four flexible online modules that were designed are aligned with the main preceptor roles: role model, educator, mentor and assessor. The program also included a small-group online interactive networking session and an online discussion forum. Following implementation, 28 pharmacist preceptors completed the training. Preliminary feedback on the training program was extremely positive, particularly to the interactive networking activity. Future programs will continue to be adapted to reflect stakeholder feedback and optimize student placement experiences.